One piece of the puzzle: developing an empirically informed open-ended student evaluation of teaching - Woodzicka, Julie A.; Greer, Lisa; Murdock, Karla Klein; Johnson, Dan R.; Locy, Toni; Goldsmith, Arthur H. (Frontiers in Education, 2025)
We describe the process undertaken by a six-person faculty committee at Washington and Lee University to develop an open-ended empirically informed student evaluation of teaching (SET) and a process to guide interpretation of SET results. Our work focused on (1) Identifying empirically based principles and resources to guide SET development; (2) Developing and pilot-testing a new SET instrument; and (3) Creating a process for faculty and department heads to summarize SET responses and use them in formative and summative assessment. Importantly, our SET instrument was created to elicit shoulds (characteristics that have been empirically associated with positive learning outcomes that students are able to validly assess) and to avoid eliciting should nots (characteristics that have not been reliably associated with positive learning or that students are not able to validly assess). Pilot testing of our SET (N = 99 student participants) evaluated the following seven areas of teaching effectiveness: setting clear expectations, creating a welcoming environment, providing encouragement and challenge, actively engaging students in learning, explaining the purpose of activities and assignments, clarifying the relevance of material beyond the classroom, and providing actionable feedback on student work. It is our hope that this summary of our process, from articulating guiding principles to bringing the SPoT (Student Perceptions of Teaching) instrument and accompanying materials before the Faculty for approval, provides guidance for other institutions seeking to create their own SET instrument and process. Our committee emphasizes the necessity of using SETs in concert with multiple additional methods of assessing teaching effectiveness within a holistic framework.